Glutamine treatment attenuates hyperglycemia-induced mitochondrial stress and apoptosis in umbilical vein endothelial cells - Sher Zaman Safi (Clinics, 2015)
OBJECTIVE:The aim of this study was to determine the in vitro effect of glutamine and insulin on apoptosis, mitochondrial membrane potential, cell permeability, and inflammatory cytokines in hyperglycemic umbilical vein endothelial cells.MATERIALS AND METHODS:Human umbilical vein endothelial cells were grown and subjected to glutamine and insulin to examine the effects of these agents on the hyperglycemic state. Mitochondrial function and the production of inflammatory cytokines were assessed using fluorescence analysis and multiple cytotoxicity assays. Apoptosis was analyzed by the terminal deoxynucleotidyl transferase dUTP nick end-labeling assay.RESULTS:Glutamine maintains the integrity of the mitochondria by reducing the cell permeability and cytochrome c levels and increasing the mitochondrial membrane potential. The cytochrome c level was significantly (p<0.005) reduced when the cells were treated with glutamine. An apoptosis assay revealed significantly reduced apoptosis (p<0.005) in the glutamine-treated cells. Moreover, glutamine alone or in combination with insulin modulated inflammatory cytokine levels. Interleukin-10, interleukin-6, and vascular endothelial growth factor were up-regulated while tumor necrosis factor-α was down-regulated after treatment with glutamine.CONCLUSION:Glutamine, either alone or in combination with insulin, can positively modulate the mitochondrial stress and cell permeability in umbilical vein endothelial cells. Glutamine regulates the expression of inflammatory cytokines and maintains the balance of the mitochondria in a cytoprotective manner.